Dielectric properties of (1−x)KNbO3−xNiO two-phase composites. (18th September 2017) - Soni, R; George, R; Joshi, D C; Nayak, S; Pramanik, P; Suresh, P; Dar, T A; Thota, S
Abstract: We report a detailed study on structural and dielectric properties, Raman scattering, and ac-conductivity of ferroelectric KNbO3 and antiferromagnetic NiO two-phase composites [( 1 ​ ​ − ​ ​ x ) KNbO3   +   x NiO]. Two major transitions were observed in the temperature dependent relative dielectric permittivity ϵ r ( T )—the first at 445   ∘ C ( T ∗ ) and the second at 220   ∘ C ( T 1 )—respectively associated with the structural transitions from tetragonal to cubic and orthorhombic to tetragonal phases. In addition, a new anomaly across T 2   ̃   320   ∘ C has been observed in ϵ r ( T ), and the loss-tangent (Tan δ (T)), which may be associated with the combined effect of antiferromagnetic ordering of NiO and ferroelectric coupling of KNbO3 . The dispersive nature of T ∗, and the Vogel–Fulcher temperature dependence of its characteristic relaxation frequency reveals the existence of relaxor-like behavior, which is further supported by Uchino–Nomura criteria (for x   ⩽   0.10 ) but departs from relaxor behavior for x > 0.10 . Temperature dependent ac-resistivity analysis ρ a c ( T ) provides strong evidence for a Mott's Variable range hopping process of charge carriers between localized states, with average hopping length of 4.2 nm and hopping energy 0.72 eV. The variation of T ∗, T 1 and T 2 as a function of x, in consonance with the crystal structure, has been discussed. Raman spectroscopic studies were carried out to study the local structure of the ( 1 ​ ​ − ​ ​ x ) K N b O 3   +   x NiO two-phase composites, which shows significant increase of tilt-angle between adjacent N b O 6 octahedra as the divalent Ni occupies octahedral sites of the K N b O 3 matrix. All the Raman-active modes of these composites are indexed as lattice translations, specifically with the motion of K + (190 c m − 1 ), the core vibrations of the N b O 6 octahedra (220 c m − 1   ⩽   ν   ⩽  320 c m − 1 ) and their collective modes (50 c m − 1   ⩽   ν   ⩽  150 c m − 1 ), and Magnon modes (2M  ̃  1500 c m − 1 ) associated with the antiferromagnetic ordering of NiO.